Protestant epistolary counselling in early modern England, c. 1559-1660 - Busfield, L (2016)
My thesis argues for the significance of individual spiritual counselling within post-Reformation English Protestantism. In particular, it demonstrates the prevalence of pastoral letter-writing and explores the purpose and dynamics of these networks. This research represents the first large-scale, comparative examination of a frequently neglected topic. It draws on many little-known letter collections and a number of unexplored manuscripts, alongside some more familiar epistolary sources. Chapter one situates my research in relation to existing literature on individual spiritual counselling and confession. As a counterpoint to the scholarly claim that contemporary accounts of the post-Reformation ministry emphasise the centrality of preaching at the expense of almost all other pastoral functions, I demonstrate the importance which many divines attributed to directing individual consciences, as well as highlighting contemporary thought on the role of the laity as providers of religious counselling. Chapter two uses Nehemiah Wallington's manuscript volume of exemplary spiritual correspondence to demonstrate the importance of epistolary counselling in the ministries of several early modern clergymen. The second section of the chapter argues that Wallington's own engagement with epistolary counselling ultimately served to uphold ministerial authority. Chapter three investigates the spiritual letter-writing relationships of early seventeenth-century Protestant ministers and their gentry patrons and demonstrates the significant potential which existed for clergymen to exercise religious agency and influence with pious elites. Chapter four explores the authoritative and spiritually intimate correspondences in which Richard Baxter engaged with laypeople from across the social spectrum during the 1650s. Current knowledge of his counselling of the Derbyshire gentlewoman, Katherine Gell, is extended through an original reflection on the significance of networks of pastoral direction in early modern English Protestantism. Chapter five explores the nature of religious advice-giving amongst the laity and uncovers its pious motivations. This characteristically 'godly' activity is both compared and contrasted with contemporary clerical counselling.